The Effect of Yoga Exercise on the Sleep Quality of Trimester III Pregnant Women - Nurmala Panjaitan; Achmad Fauzi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Pregnancy is a special situation for a woman as a prospective mother, because during pregnancy there will be many changes. Entering the third trimester, physical and psychological changes occur. This condition causes pregnant women to experience sleep disturbances. The purpose of this study was to determine the effect of yoga exercise on the sleep quality of third trimester pregnant women at BPM Nurmala Cibarusah. Methods : This study employs a pre-experiment one group pre-post test design. This study's population included all pregnant women aged 28-36 weeks at BPM Nurmala Cibarusah, with a total of 20 pregnant women and a total sample of 20 pregnant women utilizing a proportional random sampling technique. The independent variable is yoga exercise, while the dependent variable is third trimester pregnant women's sleep quality. The PSQI was employed as the study instrument, and the Willcoxon statistical test (a = 0.05) was used to analyze the results. Results : According to the findings of this study, 19 pregnant women (95.0%) had poor sleep quality prior to the implementation of yoga, but the quality of sleep improved to 19 pregnant women (95.0%) after the implementation of yoga. The Willcoxon test yields p=0.000, indicating that p0, 05, i.e. H1, is accepted. Conclusions : The conclusion from the results of this study indicates that there is an effect of yoga exercise on the sleep quality of third trimester pregnant women at BPM Nurmala Cibarusah.